ESTABLISHMENT OF INTELLIGENT CHARACTER EDUCATION THROUGH APPROACH TO LEARNING - Indra Saputra; Neviyarni; Herman Nirwana (Literasi Nusantara, 2021)
Character education is one of the important and needed educations in the development of students, for that we need to instill this intelligent character education, of course, intelligent character education cannot just grow within students, we need several approaches, one of which is an approach In learning, the purpose of this research is to find out how approaches in learning can shape intelligent character education. The methodology used in this research is a literature study with a descriptive narrative approach. The results of this study are approaches in learning that can support the formation of intelligent character education, namely quantum learning which is based on suggestions that can and will definitely affect learning outcomes, active learning which has the principle of optimizing the use of all the potential that exists in children, accelerated learning which is a A learning technique that adopts the concept of using various inputs in parallel, the last one is hypno teaching where this learning aims to reduce the frequency of brain waves so that students become comfortable and more receptive to suggestions in accepting positive values from the learning process.